The hypothesis of formation of the structure of surfaced metal at the surfacing based on the application of the prognostic algorithm of control the electrode wire speed - Lebedev V. A.; Novykov S. V. (Журнал інженерних наук)
The growth of a drop in the process of surfacing by a consumable electrode is characterized by a linear dependence of the current change on time. A hypothesis has been put forward, according to which a reduction in the feed rate of the electrode wire to zero in this time interval will substantially reduce the spraying loss and improve the formation of the surfacing roller. For the implementation of which, the use of regulators with a typical law of regulation is proposed, but not according to the current value of the arc current, but according to the forecast. A key feature of these researches is a realization given surfacing process with the imposition of external mechanical oscillations with specified amplitude-frequency characteristics on the welding bath. Analytical calculation of the transfer function for the prognostic PID regulator with the simplest linear prediction taking into account the oscillation of the weld pool is given.